Adolescent traumatic brain injury leads to incremental neural impairment in middle-aged mice: role of persistent oxidative stress and neuroinflammation - Chen, Ziyuan; Wang, Pengfei; Cheng, Hao; Wang, Ning; Wu, Mingzhe; Wang, Ziwei; Wang, Zhi; Dong, Wenwen; Guan, Dawei; Wang, Linlin; Zhao, Rui (Frontiers in Neuroscience, 2023)
Background: Traumatic brain injury (TBI) increases the risk of mental disorders and neurodegenerative diseases in the chronic phase. However, there is limited neuropathological or molecular data on the long-term neural dysfunction and its potential mechanism following adolescent TBI. Methods: A total of 160 male mice aged 8 weeks were used to mimic moderate TBI by controlled cortical impact. At 1, 3, 6 and 12 months post-injury (mpi), different neurological functions were evaluated by elevated plus maze, forced swimming test, sucrose preference test and Morris water maze. The levels of oxidative stress, antioxidant response, reactive astrocytes and microglia, and expression of inflammatory cytokines were subsequently assessed in the ipsilateral hippocampus, followed by neuronal apoptosis detection. Additionally, the morphological complexity of hippocampal astrocytes was evaluated by Sholl analysis.The adolescent mice exhibited persistent and incremental deficits in memory and anxiety-like behavior after TBI, which were sharply exacerbated at 12 mpi. Depression-like behaviors were observed in TBI mice at 6 mpi and 12 mpi. Compared with the age-matched control mice, apoptotic neurons were observed in the ipsilateral hippocampus during the chronic phase of TBI, which were accompanied by enhanced oxidative stress, and expression of inflammatory cytokines (IL-1β and TNF-α). Moreover, the reactive astrogliosis and microgliosis in the ipsilateral hippocampus were observed in the late phase of TBI, especially at 12 mpi. Conclusions: Adolescent TBI leads to incremental cognitive dysfunction, and depression-and anxiety-like behaviors in middle-aged mice. The chronic persistent neuroinflammation and oxidative stress account for the neuronal loss and neural dysfunction in the ipsilateral hippocampus. Our results provide evidence for the pathogenesis of chronic neural damage following TBI and shed new light on the treatment of TBI-induced late-phase neurological dysfunction.